2011
DOI: 10.1039/c1cp21160a
|View full text |Cite
|
Sign up to set email alerts
|

CO oxidation catalyzed by a single gold atom: benchmark calculations and the performance of DFT methods

Abstract: Quantum chemical calculations were carried out on CO oxidation catalyzed by a single gold atom. To investigate the performance of density functional theory (DFT) methods, 42 DFT functionals have been evaluated and compared with high-level wavefunction based methods. It was found that in order to obtain accurate results the functionals used must treat long range interaction well. The double-hybrid mPW2PLYP and B2PLYP functionals are the two functionals with best overall performance. CAM-B3LYP, a long range corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 84 publications
2
55
0
2
Order By: Relevance
“…1,74,75 The above ten functionals were then used to compute the relative barrier heights and the E CO 2:S N 2@C:S N 2@N relative distribution for these three reactions. The BW and CI parameters were used to check the robustness of the remaining functionals.…”
Section: Discussionmentioning
confidence: 99%
“…1,74,75 The above ten functionals were then used to compute the relative barrier heights and the E CO 2:S N 2@C:S N 2@N relative distribution for these three reactions. The BW and CI parameters were used to check the robustness of the remaining functionals.…”
Section: Discussionmentioning
confidence: 99%
“…Whether supported singly dispersed Au atoms are active for CO oxidation remains unknown. Although theoretical calculations suggested that single Au atoms could be catalytically active for CO oxidation [53], there is, however, no experimental evidence to fully demonstrate that supported single Au atoms can provide appreciable activity for CO oxidation. It has been reported that cationic Au species dispersed on oxide supports showed activity for CO oxidation at room temperature; however, their activity was much lower than that of the small Au nanoparticles [18,54,55].…”
Section: Experimental Datamentioning
confidence: 98%
“…43 The charge state of the Ni adatom is tentatively assigned to positive as the Ni 2p core-level spectrum shifts to higher binding energy in Figure 4a; however, caution is required due to final state effects in core-level PES. 44 Further insight into the Ni charge state can be obtained from the Bader charge analysis on the basis of the DFT calculations.…”
Section: Discussionmentioning
confidence: 99%